A vitrine da inclusão e o espetáculo de Nicolau: a ascensão profissional da mulher acadêmica em cargos de gestão em instituições de ensino superior no Brasil - Herrera, Vânia Érica (2019)
It is introduced the process of ascension and barriers which arise for women in management positions in Higher Education Institutions in Brazil. It aims to analyze existing barriers for academic women in management positions in Higher Education Institutions, under the views of metaphors, both those developed during the paper, as the Showcase of Inclusion and the Nicholas’ Show, as those already existing in the literature as Glass Ceiling, Crystal Labyrinth, Glass Abyss, and Sticky Floor. After surveying the gender of the Rectors, Vice-Rectors and Pro-Rectors in public and some private HEIs, seven women managers were interviewed, being two Rectors, two Vice-Rectors and three Pro-Rectors in different regions of Brazil. It was verified that there are multiple barriers to ascendancy and also to stay in management positions, mainly because they are women and the thought, even within academia as in society, is still androcentric. It can be determined that as it occurs in other types of organization, there is still prejudice regarding women in management positions in educational institutions. The barriers are numerous and still impair the professional progress of a large number of women, who often, in the middle of the career, end up giving up the goal even, most of the time, being much more qualified than men for the desired function